The Determination of Antioxidant Activity of Ethanol Extracts of Gynostemma Pentaphyllum: The determination of antioxidant activity of Gynostemma Pentaphyllum extracts - Ansafovna Nizamova, Alfina; Khalitovna Galiakhmetova, Elvira; Sergeevich Mochalov, Konstantin; Olegovich Bokov, Dmitry; Farnam, Golrokh; Vladimirovna Kudashkina, Natalia (Iranian Journal of Pharmaceutical Sciences, 2021)
Inflammatory reactions of active radicals play a primary role in many vital circumstances, and if they are not neutralized and persist in the body, many diseases will occur. Antioxidants are the very critical resources available in the body to eliminate these free radicals. Medicinal herbs have been used extensively in the treatment of diseases for centuries. Gynostemma Pentaphyllum is grown in many different locations of Europe and Asia is an adaptogenic plant that is rich in antioxidants. During this study, the antioxidant effects of Gynostemma Pentaphyllum extract are evaluated using two different methods of adrenaline autooxidation and Chemiluminescence, both patented in Russia. Our results show that the organic solvent is more suitable for the extraction of these antioxidants with the ratio of 70% ethanolic extract being yield in more extraction. This preliminary work might open a new door for future studies on the antioxidant effects of this herb grown in Russia for the treatment of inflammations and other diseases with such pathology.